Commodity Based Extension System Through Commodity Interest Group Approach (Indian Journal of Extension Education, 2012)
The present study was carried out in eight districts of Karnataka during the year 2012-13. The Community Based Tank Management Project Consultancy Services (CBTMPCS) at University of Agricultural Sciences, Bangalore established 22 Commodity Interest Groups (CIGs) in its operational area. Sincere efforts were made to motivate and encourage farmers in these 22 villages to organize Commodity Interest Groups of their own choice enrolling 20 members in each group with the financial and technical support from CBTMPCS and implemented various activities which include creation of revolving fund of ` 50, 000 /- for the use of their members. Establishing integrated crop management (ICM) demonstrations on 22 agricultural/horticultural crops covering 141.90 ha area involving 467 CIG members, procurement of packing and branding materials worth of ` 25,000/- to each CIG and developing marketing linkage with the recognized marketing agencies/organizations were the major initiatives. As a result of working of farmers in groups through CIGs and by adopting all the recommended technologies it was possible to increase overall crop yields by 29.11 per cent and water use efficiency (WUE) by 48.98 per cent and thus saving 6950.00 ha. cm water in the demonstrated area of 141.90 ha, besides securing net income of ` 250.34 lakhs by 467 farmers (CIG members).From this, it is evident that Commodity Interest Groups can play a vital role in bringing cohesiveness among group of farmers to collectively plan, mobilize resources, carry out the designed activities more systematically to secure increased production and net income to the members through organized marketing which saves time, money and labour.